VíkingAR : rebuilding an augmented reality experience - Elvar Þór Sævarsson 2001-; Helgi Steinarr Júlíusson 2000-; Ingólfur Sigurbjörnsson 1997-; Ríkharður Aron Eiríksson 2001- (2024)
New Reality has tasked us with remaking an augmented reality game in Unreal Engine 5. The game is a history lesson based on a naval battle from the age of Sturlungs and is available to play at the 1238 museum in Sauðárkrókur. Players use a tablet to interact with a topographical map of Húnaflói, where the tablet’s camera projects game assets like the ocean, ships and other elements onto the physical map. The game is short, taking less than five minutes to play. Initially, New Reality intended to fix bugs and performance issues in the old game built in Unreal 4.x, but quickly found that to be a deeply nested problem so they decided the only viable solution was to remake it from the ground up and move to Unreal Engine 5.x. We were tasked with that problem. We were given considerable freedom in how we wanted to implement said re-creation and had access to all the assets and code from the previous version, with the main requirement being to follow the same narrative and story. They also wanted us to explore viable tracking solutions to preferably replace an unappealing red marker used to centre the game world on the table.